Remote Control Time Delay Switch With Sensor - Welix, Khoo (Universiti Sains Malaysia, 2005)
The infrared remote control is commonly seen around the house nowadays. Its usage can be seen ranging from TV, video player, CD player and so on. Recently, even the fans have employed the usage of infrared remote control. However, all of these infrared remote controls can only control one and only one electrical appliances at once. Thus, it will be more useful to design an infrared remote control learning switch that has the ability to learn the code from different infrared remote control sets and perform switching operations when data are sent. This project is dedicated to implementing switching using any infrared remote control in the market. It has a learning ability which makes it user friendly and eliminates the restriction whereby the user needs to use a dedicated infrared remote control. The user can use any infrared remote control to control four of the switches. Apart from that, by using a light sensor, implemented using a light dependant resistor (LDR) it can also scan the light intensity from the environment and turn on or off a light as needed. The amount of light intensity that is needed to turn off the lights can also be adjusted from the light sensor via a variable resistor. This gives the user freedom to adjust the light sensor to suit their needs. The design also comes with a door sensor where when activated, will sense the number of people going into a room. Once the first person enters the room, it will turn on the light. And when the last person exits the room, the lights will turn off automatically. Although this project is discussed mainly using lights, in practice, it can be used with any loads and have been tested with both inductive and resistive loads. The design is controlled using the Microchip PIC 16F84A microcontroller. The programming is done using the PIC microcontroller assembly language and the hardware used to flash the hex code into the microcontroller is the F84 programmer. The program used to flash the hex code into the microcontroller is Nigel Goodwin’s WinPICProg version 1.91. As for the switching part, triac switch and relay switch are also discussed here.